«Rompo tus miembros uno a uno» (Pablo Neruda). De la reificación a la destrucción en la iconografía literaria de la amada - Bengoechea, Mercedes (Cuadernos de Trabajo Social, 2006)
Violence exerted against women occurs in a context which makes it possible and constant, and becomes cognitively accepted as «natural» only because of a series of hegemonic cultural practices which regu- late our behaviour, desire, tastes and needs. Some of the most relevant hegemonic practices are symbolic (words, discourses, images), which create and re-create a certain world view, inscribe gender violence n male and female bodies, and cooperate to make men and women accept aggressive or vulnerable exualities espectively. A constant feature in most hegemonic symbolic practices is «women’s symbolic nnihilation» n this paper I ill present some of women’s «symbolic annihilation»processes in public discourse, especially n men’s heterosexual love poetry, rying to establish a link between women’s symbolic annihilation nd physical violence against women by their lovers and artners.